Assessment of effectiveness of oral supplementation of isolated fiber of carrot on metabolic parameters in mature rats - Maria Rosana Ramirez; Debora Manuale; Juan Carlos Yori (Food Science and Human Wellness)
The present study was conducted to evaluate the metabolic effects of isolated fiber of carrot supplementation in rats. Physicochemical properties of fiber were determined. The groups were as follows: animals fed a standard diet, control group; high fiber supplementation (70 mg); low fiber supplementation (35 mg); for 12 weeks. Blood samples were collected at the time of sacrifice. The weights of heart, liver, kidneys and spleen of the experimental rats with respect to body weight were recorded. Commercial kits were used to determine serum glucose concentration, lipid profile (cholesterol, HDL-cholesterol, triglycerides), and the two main aminotransferases glutamic-oxalacetic transaminase (GOT)/glutamate-pyruvate transaminase (GPT). A histopathological assay was performed on the heart, liver, and spleen tissues of animals. Supplementation with fiber favors weight loss in female ((242.03 ± 23.73)−(197.81 ± 10.45) g); and male rats ((262.50 ± 32.21)−(213.96 ± 12.56) g) and induces a decrease in glucose levels in the supplemented animals. With the exception of total high-density lipoprotein cholesterol, the other lipid fractions decrease significantly in rats supplemented. Fiber supplementation did not induce changes in the dissected organs of the supplemented animals. In conclusion supplementation of fiber, improves glucose control, lower plasma lipid concentrations and reduced body weight in normal rats.